FIGURE 6. Chitonaster johannae. USNM E13501. A in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 6. Chitonaster johannae. USNM E13501. A. (inset) Coelomic view of abactinal surface showing overlapping plates with papular pores absent. USNM 1018953 B. Abactinal surface. C. Close up of abactinal surface showing granules and pedicellariae. D. Abactinal view of armtip showing rows of spines/granules. E. Actinal surface. F. Lateral view showing marginal plate series. USNM E13501.G. Close up of actinal intermediate and furrow area with trivalve pedicellariae. Scale Bar= 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 16, DOI: 10.5281/zenodo.276783